2019
DOI: 10.3389/fpsyg.2019.01814
|View full text |Cite
|
Sign up to set email alerts
|

12 h Abstinence-Induced ERP Changes in Young Smokers: Electrophysiological Evidence From a Go/NoGo Study

Abstract: Decreased inhibition control ability and increased craving may be the most important causes of relapsing in smoking. Although inhibition control defects in young smokers were investigated, the effects of short-term abstinence on inhibition control in young smokers were still unclear. Thirty young smokers participated in the present study. The EEG signals during the Go/NoGo task were recorded in both satiety and 12 h abstinence conditions. The task performances were observed and compared between the two conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 49 publications
0
13
2
Order By: Relevance
“…Many studies have proven that psychological symptoms, such as anxiety and depression, can lead to cognitive impairments. Previous studies have focused on nicotine abstinence for more than 12 h (11,19,31,40,41) and found a reduction in both P3a and P3b amplitudes, which indicated that 12-h nicotine abstinence may cause neurocognitive impairments (19). However, in this study, ERP P300 was measured after 2 h of tobacco abstinence, which prevented cognitive status from being induced by psychological symptoms.…”
Section: Discussioncontrasting
confidence: 57%
See 1 more Smart Citation
“…Many studies have proven that psychological symptoms, such as anxiety and depression, can lead to cognitive impairments. Previous studies have focused on nicotine abstinence for more than 12 h (11,19,31,40,41) and found a reduction in both P3a and P3b amplitudes, which indicated that 12-h nicotine abstinence may cause neurocognitive impairments (19). However, in this study, ERP P300 was measured after 2 h of tobacco abstinence, which prevented cognitive status from being induced by psychological symptoms.…”
Section: Discussioncontrasting
confidence: 57%
“…Studies have confirmed that nicotine can reach the brain in 10-20 s, and brain nicotine concentrations increase after smoking each cigarette and then decline over 20-30 min as nicotine redistributes to other organs or tissues; the average nicotine half-life in body tissues is 2 h (39). Previous studies that investigated nicotine abstinence on cognitive control function focused on nicotine deprivation for more than 12 h (11,19,31,40,41) but could not avoid confounding the cognitive control impairment induced by pure nicotine abstinence and the psychological symptoms produced by nicotine abstinence.…”
Section: Introductionmentioning
confidence: 99%
“…40 Hence, by comparing the latency and amplitude of the same component under different conditions, we can test whether different conditions lead to different brain activations at specific time points. According to previous studies, both N2 and P3 components are related to inhibition in cognition tasks (such as the Go/NoGo task) 19,37 and problemsolving related tasks (such as the Piaget-like task). 28,34 Studies showed that the amplitude of the N2 component was larger in the No-Go condition when inhibition was typically involved than in the Go condition.…”
Section: Introductionmentioning
confidence: 93%
“…Abstinence from smoking disrupts cognitive performance that may help maintain smoking behavior (9,10). Previous studies reported that a general performance monitoring system involving a range of cognitive functions after acute abstinence from smoking may be a neurophysiological indicator (11).…”
Section: Introductionmentioning
confidence: 99%